With three steps we are not forced to complete all the steps before continuing interacting with other context around the two initial letters.
In fact, Révész himself answers this question, in his Introduction to Formal Languages at archive.org, with the following example.
Note that three rules like AB → A'B, A'B → A'D, and A'D → CD are
not enough to replace the rules AB → CD. For example, if we have the
rules S → AB, B → DE, AB → CD in the original grammar, then this
replacement makes the derivation
S ⇒ AB ⇒ A'B ⇒ A'DE ⇒ CDE
possible, though CDE is not derivable in the original grammar. Such
parasitical derivations are often quite difficult to avoid when we are trying
to transform a grammar into an equivalent one.